2022
DOI: 10.1016/j.omtn.2021.12.024
|View full text |Cite
|
Sign up to set email alerts
|

METTL14-mediated Lnc-LSG1 m6A modification inhibits clear cell renal cell carcinoma metastasis via regulating ESRP2 ubiquitination

Abstract: Clear cell renal cell carcinoma (ccRCC) is the most lethal urological cancer and is characterized by a high rate of metastasis and relapse. N6-Methyladenosine (m 6 A) is implicated in various stages of cancer development. However, a thorough understanding of m 6 A-modified lncRNAs in ccRCC is lacking. The results showed that METTL14 had decreased expression in ccRCC tissues. In addition, the expression of METTL14 was negatively correlated to the prognosis, stage, and ccRCC tumor grade. The silencing of METTL14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…Methylation modifications and lncRNAs affect tumorigenesis and progression through a complex regulatory network. A study revealed that the m6A reader YTHDC1 blocked ubiquitination between lncRNA LSG1 and ESRP2 and inhibited the advancement of renal cell carcinoma [ 32 ]. By altering the stability of lncRNA ZFAS1, the m6A methyltransferase METTL3 influenced autophagy and the development of nasopharyngeal cancer cells [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methylation modifications and lncRNAs affect tumorigenesis and progression through a complex regulatory network. A study revealed that the m6A reader YTHDC1 blocked ubiquitination between lncRNA LSG1 and ESRP2 and inhibited the advancement of renal cell carcinoma [ 32 ]. By altering the stability of lncRNA ZFAS1, the m6A methyltransferase METTL3 influenced autophagy and the development of nasopharyngeal cancer cells [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, studies about lncRNA have drawn much attention in various cancer fields. Many lncRNAs can be modified by specific m6A modulators to participate in the tumorigenesis and development (18)(19)(20). Studies have documented that lncRNAs can serve as competitive endogenous RNAs to target m6A modulators, influencing vital cellular functions (21).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence demonstrated that the lncRNAs play the key role in the progression of, and immunotherapy for, cancers [ 19 ], while the lncRNAs are regulated by the m6A regulators [ 20 ]. To elicit the correlation between the m6A regulators and lncRNAs, we performed the WGCNA on the TCGA-LUAD cohort, incorporating differentially expressed lncRNAs to identify the key module most closely related to the m6A regulators ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%